Mucocutaneous Kaposi's sarcoma in an HIV-positive patient: diagnosis and treatment - Carvalho,Laura Priscila B. (2016)
ABSTRACT Kaposi's sarcoma (KS) is an endothelial neoplasia caused by infection with the human herpesvirus 8 (HHV-8), and the type associated with the human immunodeficiency virus (HIV) is considered the most aggressive and frequent. This paper reports a case of mucocutaneous KS in a patient not formerly aware of being an HIV bearer. A 38-year-old male patient has sought treatment with multiple oral lesions and one in the skin. Serology was positive for HIV and incisional biopsy diagnosed KS. After 11 months of chemotherapy and antiretroviral therapy, there was complete remission of the skin KS and partial remission of oral lesions.